Duration of Listening to BTS Music with Psychological Well-Being in BTS Fans - Ester Kinny Pyghaiswati Allosau; Christiana Hari Soetjiningsih (Borong Newinera Publisher, 2024)
This correlational quantitative research aims to determine the relationship between the duration of listening to BTS music and the psychological well-being of BTS fans in Indonesia (known as Army Indonesia). The study included 102 participants who have been fans for a minimum of 2 years, and data was collected using a Google Form provided by the researcher. The measurement tools used were an interval scale to assess the daily duration of listening to BTS music and the Ryff Psychological Well-Being (RPWB) scale to measure psychological well-being. The research results indicate a significant positive correlation between the duration of listening to BTS music and the psychological well-being of BTS fans in Indonesia, with an